Family prayer as a tool for consolidating Abkhazian family unions - R.Sh. Zelnitskaya (Shlarba) (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper deals with family prayers typical for the Abkhazian society – three family prayers from different historical regions of Abkhazia were studied: Amparians’ prayer (the Bzyb Abkhazia), Aibaians’ prayer (the Bzyb Abkhazia), and supplication Zhapuans’ Jakhashkiar-nykha (Abzhua Abkhazia). The relevance of the research is determined by the need to study the traditional institutions and rituals in the changing Abkhazian society, because they are still the important elements of social life. Despite the fact that some Abkhazians are Christians and others are adherents of Islam, for each of them national beliefs are important. In the minds of Abkhazians, an essential part of the people’s religion is sacred places where prayers are held, sacrifices are made, and oaths are taken. Family prayers are performed by most family unions, especially by the former representatives of the highest estate and free community members. In the modern Abkhazian society, family prayers support solidarity and ethnic identity within the family, as well as the informal social status of a particular family union. The performance of a family prayer itself is an important consolidating tool for all members of a particular family union and contributes to the maintenance of ties between its members. Based on the results of the study, it was concluded that Abkhazians are aware of the danger of complete disunity, which is why they seek to preserve the traditional rituals and practices to avoid it. The findings may be of particular interest to ethnologists and sociologists engaged in the study of modernizing societies.